Analysis of Employee Performance and factor Influencing It Using the C4.5 Algorithm Method - M Lintang; N Pandiangan; Nurhayati (Technium Social Sciences Journal, 2023)
In an organization, individual performance greatly affects the performance of the organization, both government and private organizations in achieving predetermined goals. Good employee performance will have an impact on overall organizational performance, which in turn can be seen from organizational achievements. Some important factors that are taken into consideration by an employee performing well, among others; Employee salary, incentives/bonuses, work motivation, workload/quantity of work, reliability, and employability. This study uses a data mining classification approach using the c4.5 method in making a decision tree. The results of a trial of 25 datasets using the decision tree method were able to provide a conclusion that employees will be able to improve their performance if the organization provides a policy in the form of providing monthly incentives to employees as a bonus reward to those who are diligent in carrying out their work, such as having activeness and being able to work together.